Successful response to intravenous immunoglobulin as rescue therapy in a patient with Hashimoto's encephalopathy. (29th December 2010) - Cornejo, Rodrigo; Venegas, Pablo; Goñi, Daniela; Salas, Alvaro; Romero, Carlos
Abstract : The authors describe the case of a 61-year-old woman who was admitted to our intensive care unit (ICU) due to impaired consciousness associated with generalised seizures. Her cerebrospinal fluid, electrolytes, acid-base analysis, and common laboratory and toxicology tests were normal. An MRI ruled out the presence of stroke or haemorrhage but showed severe leukoencephalopathy. Parkinson's disease, Creuzfeld–Jacob disease, vascular alterations, cancer, and rheumatological and metabolic diseases were evaluated and excluded. In view of her history of hypothyroidism despite adequate hormonal replacement and clinical behaviour, Hashimoto's encephalopathy was considered. Anti-thyroperoxidase levels were above 3000 IU/ml. The patient received 5 g of methylprednisolone followed by prednisone, but after a favourable initial response, returned to a comatose state. However, after administration of intravenous immunoglobulin (IVIG) 2 g/kg, the patient recovered with resolution of neurological symptoms and was discharged from the ICU 4 days after finishing IVIG treatment.